The 8th National Gastric Cancer Academic Conference: focus on specification, translational research, and plan - Dai, Ni (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
The 8th National Gastric Cancer Academic Conference, organized by Gastric Cancer Association of Chinese Anti-cancer Association and co-hosted by Beijing Cancer Hospital, Chinese Journal of Cancer Research (CJCR), Translational Gastrointestinal Cancer (TGC), Chinese Journal of Gastrointestinal Surgery, and Chinese Journal of Practical Surgery, was held at Beijing International Convention Center from June 15 to 16, 2013.